EFEKTIVITAS PEMBELAJARAN MATEMATIKA BERBASIS IT (GEOGEBRA) DALAM MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA SMA N 1 BATANG ANGKOLA - Hamid Marpaung, Paisal; Hidayat, Thofik; Halomoan Siregar, Alfiansyah; Sahara, Nur; Fuady Dharma Harahap, Andes; Dongoran, Awaluddin; Rahmadani, Seri (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2021)
The low ability of students to solve mathematical problems is one of the causes of the low student achievement in mathematics. There are many factors that cause this to happen, one of which is learning mathematics which is monotonous or lacks variation. For that, learning mathematics using IT during the teaching and learning process, in this case the Geogebra application. As one of the efforts made, of course, it is expected to improve students' mathematical problem solving abilities. Therefore, this study aims to determine whether the geogebra software can improve students' mathematical problem solving skills in the SPLDV material. The sample in this study were 35 students of class X IIS 1 in SMA Negeri 1 Batang Angkola with virtual research and using a qualitative approach.